HUBUNGAN INFERTIL DENGAN RESPON PSIKOLOGIS ISTRI YANG MENGALAMI INFERTIL DI KOTA PADANG TAHUN 2015 - Eka Sari, Dian Juni; Hadi, Dasman; Oktriani, Tuti (LPPM Universitas Prima Nusantara Bukittinggi, 2017)
Smoking is one of the common habits encountered in everyday life. Lifestyle or lifestyle is interesting as a health problem, at least considered as a risk factor of various diseases. Perhaps people already understand the danger, because in every pack of cigarettes there is a warning smoking can cause cancer, heart attacks, impotence and disruption of pregnancy and fetus. From these warnings, it can be clearly known that smoking has a bad effect on pregnancy and the fetus in the womb. Smoking habits of the prospective mother was a bad result in the child who will be born. There is strong evidence that pregnant women who smoke can directly affect and impair the development of the fetus in utero, the most common is low birth weight. Pregnant women who are both smokers and passive smokers are at high risk of causing harm to both the baby and himself. Children conceived to tend to lose weight, sometimes the baby is born under normal weight, the baby is born prematurely. Based on Indonesia's estimates and demographic and health surveys, the national LBW rate in the 2002-2003 period reached 7.6%. While in West Sumatra Province, the number of LBW in 2005 reached 2210 people and inÂ Payakumbuh the incidence of BBLR in 2005 reached 68 people. Based on preliminary survey data, Sarilamak's work in the work area of Tanjung Pati Health Clinic of Lima Puluh Kota District has 9 babies with birth weight less than 2500 gram. After 5 pregnant women were asked about their husbands' smoking habits, 4 of them answered that their husbands smoked and spent more than 10 cigarettes per day and 1 person answered her husband did not smoke. The purpose of this study is to see the relationship of husband knowledge about the impact of passive smokers on pregnant women on the husband's attitude about smoking in Kenagarian Sarilamak Work Area Puskesmas Tanjung Pati Year 2016. This study is analytic, the population in this study amounted to 36 respondents, using total sampling technique. Data were collected using a questionnaire, the study was conducted in November 2016.